2003
DOI: 10.1089/105072503322401078
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Maternal Iodine Status and the Relationship to Neonatal Thyroid Function

Abstract: Iodine deficiency in the postpartum period has the potential to affect neonatal neuropsychointellectual development. We performed a cross-sectional study involving 50 postpartum women and their neonates, measuring maternal urine iodine, breast milk iodine, and neonatal thyroid stimulating hormone (TSH), and examining their interrelationships. Women were studied at a median (range) of 4 (3-9) days postpartum. Moderate to severe iodine deficiency (defined by urine iodine concentration < 50 microg/L) was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 13 publications
4
39
5
Order By: Relevance
“…The median iodine content in breast milk was lower than this in our study. Similarly to other published data, we also observed a positive correlation between the iodine content of breast milk and that of the nursing infant's urine (27)(28)(29)(30)(31)(32)(33)(34)(35). Considering that all of the women were breast-feeding on day 3 and 58% were doing so 3 months later, a high percentage of the infant population in the study area were probably not getting adequate iodine for thyroid hormone synthesis and storage (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The median iodine content in breast milk was lower than this in our study. Similarly to other published data, we also observed a positive correlation between the iodine content of breast milk and that of the nursing infant's urine (27)(28)(29)(30)(31)(32)(33)(34)(35). Considering that all of the women were breast-feeding on day 3 and 58% were doing so 3 months later, a high percentage of the infant population in the study area were probably not getting adequate iodine for thyroid hormone synthesis and storage (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 86%
“…This is particularly relevant to the complications of ID because breast milk is usually the only source of iodine for newborns. Breast milk iodine is considered sufficient when values are in the range of 150-180 mg=L (4,11,14,17,18,(27)(28)(29)(30)(31)(32)(33)(34)(35). The median iodine content in breast milk was lower than this in our study.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Fourthly, the FFQ retrospectively evaluates daily iodine intake over a period of time, whereas the UIC reflects iodine intake over the recent few days rather than usual intake. Lastly, it has been reported that the level of iodine intake measured by the FFQ tends to be overestimated and the reason is eral studies including our previous study [24], those in the mildly iodine-deficient areas from Australia [57][58], and in the pregnant women with extremely high UI excretion (1.2mg/L) in China [59], whose UIC positively correlated with neonatal FT 4 concentration. The exact reason for the discrepancies is not clear and further large epidemiological studies are necessary in different iodine statuses.…”
Section: Relationship Between Maternal Tsh Ft 4 Uic and Neonatal Tshmentioning
confidence: 93%